A design for manufacturing methodology using defects knowledge for aerospace product manufacturing. (September 2021) - Elsouri, Mohammed; Gao, James; Simmonds, Clive; Martin, Nick
Defects generated by the UK supply chain is much higher than its global competitors. Defects impact costs and production throughput due to unpredictable disruptions resulting in many non-value adding activities. However, defects data associated knowledge have rarely been considered and implemented as the manufacturing capability in existing design for manufacturing and assembly (DFMA) data/knowledge bases. On the other hand, current ICT systems used in the aerospace industry are not flexible enough to keep up with the new requirements of collaborating to manage knowledge properly, and the use of real-time manufacturing data generated in manufacturing activities. This research was carried out in collaboration with one of the UK's largest aerospace companies in order to analyse the complexity of design and manufacturing activities of high-value safety-critical aerospace products. The results of the work are presented, and a novel approach and system was developed, that can be used to support DFMA using defects knowledge. The approach was implemented as a knowledge management system using collaborative design principles. Key findings from the main contribution in the context of extended enterprises of high value low volume safety critical product manufacturing are discussed.